A Comprehensive Study Regarding the Intrauterine Development of Nails. (3rd April 2021) - Munteanu, Octavian; Filipoiu, Florin-Mihail; Cirstoiu, Monica Mihaela; Băloiu, Andra-Ioana; Petrescu, Ioan-Andrei; Bohiltea, Roxana Elena
ABSTRACT: The nail apparatus serves as a protective layer over the dorsal aspect of each distal phalanx of both hands and feet. Besides protection, other functions include serving as part of defense or attack mechanisms, scratching, and dexterity. Nail development has been a subject of interest since the 19th century, from both the phylogenetic and ontogenetic points of view. Despite the early spark of interest, nail embryology has yet been analyzed by a relatively small number of scientists. In the Department of Anatomy of "Carol Davila" University of Medicine and Pharmacy, we performed a morphological analysis on 41 embryos and fetuses with gestational ages that varied between 6 and 29 weeks.